Parenting Style of Parents and Temper Tantrum at the Age of 1-3 Years at Pakuhaji Health Center, Tangerang Regency in 2018 - Zulia Putri Perdani; Jamaludin Al-afghani (Universitas Muhammadiyah Tangerang, 2019)
Background: Temper tantrums are an uncontrolled emotional outbursts or anger sustained could be aggressive. Temper tantrums can be handled by one way a good parent pattern applied to children. Objective: This study aimed to determine the relationship between Parenting and Temper Tantrums in Children Ages 1-3 Years at Puskesmas Pakuhaji Kabupaten Tangerang. Research Method: The research design used in this study was analytic descriptive with a cross-sectional approach. The samples in this study were 95 respondents with a sampling technique that cluster random sampling. The analysis technique used in this study was chi-square test. Results: It shows that respondents with positive authoritarian parenting are 65 respondents (65.3%), democratic parenting as many as 55 respondents (57.9%) and positive premise parenting patterns of 56 respondents (58.9%). And temper tantrums were 63 (66.3%).The results of the analysis showed that authoritarian parenting was not related to parenting by tempering tantrums, and there was a relationship between permissive parenting and a tempering tantrums, democratic parenting had no relationship with temper tantrums. Conclusion: This means that the better the parenting style of the child, the lower the occurrence of temper tantrums.Keyword: children aged 1-4 years, parenting parents, temper tantrum.